Effects of Feeding Fermented Medicago sativa (Plus Soybean and DDGS) on Growth Performance, Blood Profiles, Gut Health, and Carcass Characteristics of Lande (Meat) Geese - Li, Hui; Liu, Yang; Wei, Lan; Lin, Qian; Zhang, Zhifei (Frontiers in Physiology, 2022)
The objective was to investigate the effects of alfalfa (Medicago sativa Linn)-mixed silage fermentation material (AMSFM) on various aspects of growth, function, and carcass characteristics of Lande (meat) geese. Based on a previous study, we used the following AMSFM: 80% Alfalfa +10% soybean meal +10% DDGS ensiled for 45 days. Lande geese, n = 264, 77 days of age, were randomly allocated into four groups with six replicates in each group. Control geese were fed a basal diet, whereas experimental groups were fed a basal diet supplemented with 6, 12, or 24% AMSFM. The experiment lasted 21 days. The AMSFM promoted some aspects of growth, with increase (p < 0.05) in leg muscle rate, lean meat rate, muscle protein content, and total energy content of leg muscle plus concurrent decreases (p < 0.05) in crude fat content and abdominal fat rate in chest muscle. In addition, AMSFM increased (p < 0.05) glutathione content in chest and leg muscles and serum superoxide dismutase activity, and it reduced (p < 0.05) muscle malondialdehyde content and serum concentrations of triglycerides, total cholesterol, urea, and aspartate aminotransferase, consistent with good liver and kidney function. Moreover, AMSFM improved (p < 0.05) ileum morphology. In conclusion, the optimal supplemented rate of AMSFM in the meat geese diet (12%) improved immunity and antioxidant status and enhanced growth performance and carcass characteristics of meat geese.